2006
DOI: 10.1143/jjap.45.5354
|View full text |Cite
|
Sign up to set email alerts
|

Newly Developed Resolution Enhancement Lithography Assisted by Chemical Shrink Process and Materials for Next-Generation Devices

Abstract: Plasma based ion implantation for a planar target was simulated using the particle-in-cell model. The plasma sheath evolution and the ion implantation details (the incident ion flux, the ion impact angle and the ion impact energy) were studied for targets with different sizes, with an aim to investigate the dependence of dose uniformity on target size. The effect of plasma density and pulse width on dose distribution was studied as a plus. The simulation results show that a larger target leads to a faster and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Since the bias obtained in through-pitch ∆CDs fluctuated within 6 nm, the reaction system proved to have uniform reactivity for various pitches. Terai et al [18] reported the cross-linking-type chemically shrinking material (ArF RELACS, Resolution Enhancement Lithography Assisted by Chemical Shrink) that had good through-pitch bias (~10 nm). Although the evaluation conditions and the resist material are quite different in the report, our results seem to demonstrate the advantage of the reaction system employed in REM-opt.…”
Section: Optimization Of Rem Solutionmentioning
confidence: 99%
“…Since the bias obtained in through-pitch ∆CDs fluctuated within 6 nm, the reaction system proved to have uniform reactivity for various pitches. Terai et al [18] reported the cross-linking-type chemically shrinking material (ArF RELACS, Resolution Enhancement Lithography Assisted by Chemical Shrink) that had good through-pitch bias (~10 nm). Although the evaluation conditions and the resist material are quite different in the report, our results seem to demonstrate the advantage of the reaction system employed in REM-opt.…”
Section: Optimization Of Rem Solutionmentioning
confidence: 99%
“…In lithography, the trend is always moving to smaller features and pushing for practical solutions [1][2][3][4][5] . For semiconductor manufacturing of low-k 1 process, as EUV and e-beam technologies are not yet mature for production [6][7][8] , immersion lithography is indispensable for process development and production 9 .…”
Section: Introductionmentioning
confidence: 99%